Ayurvedic Management of Kamala with special reference to Hepatitis A (AYUSHDHARA, 2025)
A male patient of age 17 years with clinical features of yellowish discolouration of urine, eyes, reduced appetite, nausea and gaseous discomfort, bitter taste in mouth, reduced appetite, pain in epigastrium, headache. Ayurvedic diagnosis was made of Koshtashakhashrit Kamala and modern diagnosis based on blood reports was Hepatitis A. Interventions: In this case study, different modern drugs and Ayurvedic Shamana medications were used along with Shodhana Chikitsa. Conclusion: The changes in levels of variables of LFT and patient’s clinical features were promising.